Artificial and natural selection components reveal the mechanisms of tropical sheep populations against gastrointestinal parasites - Leonardo Sartori Menegatto; Karine Assis Costa; Ricardo Dutra do Bem; Luara Afonso de Freitas; Luiza Vage Coelho Sartori; Elisa Peripolli; Nedenia Bonvino Stafuzza; Claudia Cristina Paro de Paz (PLoS ONE, 2026)
The infection by Haemonchus contortus is a significant challenge to sheep production in tropical regions, particularly in developing countries. Although several genomic studies have been conducted on this topic, there is still a lack of research combining evolutionary information on resistance and resilience to nematode infection. The aim of this study was to provide evidence of different types of selection and their effects on traits associated with infection levels and animal productivity, using pedigree, phenotypic, and genomic data. It was hypothesized that these patterns would reflect indirect artificial selection and relaxed natural selection. Phenotypic data were collected for Faecal Egg Count (FEC), Eye Color Chart (ECC), Packed Cell Volume (PCV), Total Plasma Protein (TPP), Body Weight (BW), and Body Condition Score (BCS) from 1,283 Santa Inês sheep. A total of 638 animals were genotyped using the Ovine SNP50 BeadChip. After estimating breeding values using the BLUPF90 software, statistical models were employed to assess differences in the intensities of natural and artificial selection and to identify the type of selection acting on each trait, in comparison with classic studies of sexual selection. Selection signatures were investigated using Wright’s fixation index, in addition to analyses of runs of homozygosity. The gene content of the identified regions and their associated pathways were examined using the Ensembl BioMart tool and the Panther Classification System, respectively, along with alignments of quantitative trait loci (QTL). BCS was found to be the best indirect trait correlated with parasitological traits, and selection intensity analysis showed that natural selection contributed 76%, compared to 24% from artificial selection. Traits such as BW, PCV, and TPP exhibited directional selection, while FEC and ECC varied according to the challenge level applied. A total of 15 selection signatures were identified (11 for natural selection and 4 for artificial selection), with 9 overlapping with islands of homozygosity, encompassing 131 genes and 49 QTL. A critical analysis revealed that both types of selection contribute to the phenomena of resistance and resilience. However, evidence of directional selection, hard sweeps, and functional enrichment of innate immunity was found for artificial selection, while natural selection exhibited evidence of stabilizing selection, soft sweeps, and functional enrichment of adaptive immunity.